Virulence of Shigatoxigenic and Enteropathogenic Escherichia coli O80:H2 in Galleria mellonella Larvae: Comparison of the Roles of the pS88 Plasmids and STX2d Phage - Rie Ikeda; Fanny Laforêt; Céline Antoine; Mare Adachi; Keiji Nakamura; Audrey Habets; Cassandra Kler; Klara De Rauw; Tetsuya Hayashi; Jacques G. Mainil; Damien Thiry (Veterinary Sciences, 2023)
The invasiveness properties of Shigatoxigenic and enteropathogenic Escherichia coli (STEC and EPEC) O80:H2 in humans and calves are encoded by genes located on a pS88-like ColV conjugative plasmid. The main objectives of this study in larvae of the Galleria mellonella moth were therefore to compare the virulence of eight bovine STEC and EPEC O80:H2, of two E. coli pS88 plasmid transconjugant and STX2d phage transductant K12 DH10B, of four E. coli O80:non-H2, and of the laboratory E. coli K12 DH10B strains. Thirty larvae per strain were inoculated in the last proleg with 10 μL of tenfold dilutions of each bacterial culture corresponding to 10 to 106 colony-forming units (CFUs). The larvae were kept at 37 °C and their mortality rate was followed daily for four days. The main results were that: (i) not only the STEC and EPEC O80:H2, but also different E. coli O80:non-H2 were lethal for the larvae at high concentrations (from 104 to 106 CFU) with some variation according to the strain; (ii) the Stx2d toxin and partially the pS88 plasmid were responsible for the lethality caused by the E. coli O80:H2; (iii) the virulence factors of E. coli O80:non-H2 were not identified. The general conclusions are that, although the Galleria mellonella larvae represent a useful first-line model to study the virulence of bacterial pathogens, they are more limited in identifying their actual virulence properties.